Irreverent Nature of Dissymmetry Factor and Quantum Yield in Circularly Polarized Luminescence of Small Organic Molecules - Nagata, Yuya; Mori, Tadashi (Frontiers in Chemistry, 2020)
Recently, a rational modification of small organic molecules has attracted considerable attention for designing advanced materials with enhanced circularly polarized luminescence (CPL) activity. A particular emphasis has been placed on fully allowed π-π* transition of rigid aromatic systems, due to their relatively superior emission properties or quantum yields of luminescence (Φlum). However, their dissymmetry factors (glum), differential left and right CPL intensities, are typically disappointingly low at least in one to two orders of magnitude. Truly useful organic CPL materials, rated by a circular polarization luminosity index (ΛCPL) per single molecule, possess both |glum| and Φlum values high. However, how to improve these two factors simultaneously with a proper molecular design is an open question. Here, we addressed this issue by theoretical and statistical inspection on a possible relation of the glum and Φlum values. According to the analysis, we propose simple, unpretentious, yet pertinent guidelines for designing superior organic CPL materials for the future with large ΛCPL values.